Iridoids and sesquiterpenoids of Valeriana stenoptera and their effects on NGF-induced neurite outgrowth in PC12 cells. (October 2015) - Dong, Fa-Wu; Wu, Zhi-Kun; Yang, Liu; Zi, Chen-Ting; Yang, Dan; Ma, Rui-Jing; Liu, Zhen-Hua; Luo, Huai-Rong; Zhou, Jun; Hu, Jiang-Miao
Abstract : Graphical abstract: Phytochemical research of Valeriana stenoptera resulted in isolation of many iridoids and sesquiterpenoids. Seven of these compounds showed promoting effects on NGF-induced neurite outgrowth in PC12 cells at a concentration of 10 μM. Highlights: Valeriana stenoptera analysis gave 21 iridoids and sesquiterpenoids, 10 being previously unknown. The sesquiterpenoids mainly belong to the patchoulane-type. Seven of the tested compounds showed NGF-promoting activity in PC12 cells. Abstract: Twenty-one compounds (nine iridoids and twelve sesquiterpenoids), including ten previously unknown (five iridoids and five sesquiterpenoids) were isolated from whole dried material of Valeriana stenoptera . Structures were established on the basis of extensive spectroscopic analysis and the relative stereochemistry of 13-hydroxypatchoulol A was further confirmed by X-ray crystallographic data. All isolates were evaluated for their effects on nerve growth factor (NGF)-mediated neurite outgrowth in pheochromocytoma (PC12) cells and seven compounds showed potent promoting effects.